PENGARUH PENDAMPINGAN ORANG TUA DAN DISTRAKSI BERBASIS GADGET TERHADAP TINGKAT KECEMASAN ANAK SELAMA INDUKSI ANESTESI : THE EFFECT OF PARENTAL PRESENCE AND DIGITAL DEVICE DISTRACTION ON PEDIATRIC ANXIETY LEVELS DURING ANESTHESIA INDUCTION - Arvid Muzzamille; Yusniarita Yusniarita; Rosa Delima Ekwantini; Ida Mardalena (Politeknik Kesehatan Kemenkes RI Jakarta I, 2026)
Background: Preoperative anxiety is a prevalent psychological response among pediatric patients undergoing surgery, which tends to escalate during the induction of anesthesia. Elevated anxiety levels can trigger negative behavioral manifestations—such as crying, screaming, and resisting medical procedures—while adversely affecting the anesthesia induction process, postoperative recovery, and the child's overall psychological well-being. Parental presence and the utilization of digital devices as distraction methods represent potential non-pharmacological interventions to alleviate pediatric anxiety throughout the perioperative period. Method: This study employed a quasi-experimental pretest–posttest with a control group design. The study population comprised 371 pediatric patients undergoing anesthesia at Dr. Hasan Sadikin Central General Hospital, Bandung. A sample of 60 respondents was selected via purposive sampling and allocated into either the intervention group or the control group. The intervention group received parental presence combined with digital device distraction, whereas the control group received parental presence alone. Anxiety levels were measured using the Modified Yale Preoperative Anxiety Scale (mYPAS). Data analysis was performed using the Wilcoxon and Mann–Whitney U tests due to the non-normal distribution of the data. Result: The mean difference in pre-to-postoperative anxiety scores was 11.50 in the intervention group and 10.50 in the control group. The comparative analysis of anxiety levels revealed a significant difference between the intervention and control groups during the induction of anesthesia (p = 0.047; p < 0.05).Conclusion: Parental presence integrated with digital device distraction is significantly more effective in mitigating pediatric anxiety during anesthesia induction than parental presence alone. This intervention can be recommended as a viable non-pharmacological strategy to minimize preoperative anxiety and foster a more positive perioperative experience for pediatric patients.